Living with Conflicts over Wolves. The Case of Redes Natural Park. Issue 1 (2nd January 2021) - Ottolini, I.; De Vries, J. R.; Pellis, A.
Abstract: Numerous efforts are implemented to manage conflicts over wolves with the implicit aim to predict, gain control, and resolve them. Yet conflicts over wolves tend to persist in practice. Based on Niklas Luhmann's social systems theory, we aim to explain this persistence by considering conflicts over wolves as evolving unities of persisting and contradicting communications. Using a case study in Redes Natural Park, Spain, we illustrate how conflicts over wolves evolve semi-independently through internal and external communications. These communications can both fuel and redirect the complex trajectories of conflict, thereby contributing to its persistence over time. Taking lessons from this case, we propose alternative interventions that do not necessarily aim at resolving conflicts, but instead consider an open-mindedness toward the multitude of conflict observations and experiences; the need to follow and monitor the enduring lives of conflict over wolves; and the prudence of overly managing these conflicts at a distance.